Lymphoproliferative malignancy in rheumatoid arthritis: a study of 20 cases. Issue 2 (April 1984) - Symmons, D P; Ahern, M; Bacon, P A; Hawkins, C F; Amlot, P L; Jones, E L; Prior, P; Scott, D L
Abstract : A series of 20 patients with definite or classical rheumatoid arthritis who subsequently developed a lymphoproliferative malignancy are described. The mean time between the onset of the 2 diseases was 13.2 years. A wide range of types of non-Hodgkin's lymphoma and Hodgkin's disease were found; there were no unusual histological features in the lymphomas. Although many of the patients had had gold, penicillamine, and other second-line drugs, none of them had received cytotoxic drugs, and there was no evidence that therapy was a cause of their malignancies. The likely cause of the association is a predisposition to both diseases.